Production of upgraded metallurgical-grade silicon for a low-cost, high-efficiency, and reliable PV technology - Míguez Novoa, José Manuel; Hoffmann, Volker; Forniés, Eduardo; Mendez, Laura; Tojeiro, Marta; Ruiz, Fernando; Funes, Manuel; del Cañizo, Carlos; Fuertes Marrón, David; Dasilva Villanueva, Nerea; Caballero, Luis Jaime; Arıkan, Bülent; et al. (Frontiers in Photonics, 2024)
Upgraded Metallurgical Grade silicon (UMG-Si) has the potential to reduce the cost of Photovoltaic (PV) technology and to improve its environmental profile. In this contribution, we summarize the extensive work made in the research and development of UMG technology for PV, which has led to the demonstration of UMG-Si as a competitive alternative to polysilicon for the production of high-efficiency multicrystalline solar cells and modules. The tailoring of the processing steps along the complete Ferrosolar's UMG-Si manufacturing value chain has been addressed, commencing with the purification stage that results in a moderately compensated material due to the presence of phosphorous and boron. Gallium is added as a dopant at the crystallization stage to obtain a uniform resistivity profile 1 •cm along the ingot height. Defect engineering techniques based on phosphorus diffusion gettering have been optimized to improve the bulk electronic quality of UMG-Si wafers. Black silicon texturing, compatible with subsequent gettering and surface passivation, has been successfully implemented. Industrial-type Al-Back Surface Field (BSF) and Passivated Emitter and Rear Cell (PERC) solar cells have been fabricated, achieving cell efficiencies in the range of those obtained with conventional polysilicon substrates. TOPCon solar cell processing key steps have also been tested to further evaluate the potential of the material in advanced device architectures beyond PERC. Degradation mechanisms related to light exposure and operation temperature have been shown not to be significant in UMG PERC solar cells when a regeneration step is implemented, and PV modules with several years of outdoor operation have demonstrated similar performance to reference ones based on poly-Si. Life-Cycle Analysis (LCA) has been carried out to evaluate the environmental impact of UMG-based PV technology when compared to the poly-Si-based one, considering different scenarios both for the manufacturing sites and the PV installations.